SEALS FROM THE SUBURBS OF HALYCH - HRUSHEVSKYI, Mykhailo (Halych. Scientific work collection, 2022)
In this short article, the historian analyzes in detail three pewter seals found on the territory of ancient Halych. The main attention is paid to the epigraphy of the finds, as well as the analysis of the meaning of the inscriptions.